A new stoma for an older person—An association with quality of life and physical function: A systematic review. Issue 8 (4th May 2022) - Neuberger, Lydia; Braude, Philip; Weeks, Kayleigh; Braude, Peter; Halliday, Ruth; McCarthy, Kathryn; Carter, Ben
Abstract: Background: Older people are more likely to have a stoma postabdominal surgery than younger people. Few studies have examined the effect of a stoma on older people. The aim of this review was to explore the effect of a stoma on functional independence of an older person. We explored secondary outcomes of poststoma formation length of hospital stay, quality of life and factors affecting stroma independence. Methods: An exploratory systematic review was developed by our multidisciplinary group including an expert patient, colorectal surgeon, stoma nurse, physiotherapist, geriatrician, and methodologist. Four databases were searched including studies with participants 60 years old or older, who had undergone abdominal surgery for any pathology resulting in an abdominal stoma. Results: We identified 857 studies, of which we included 25 in the final review incorporating 6972 participants (average age 67.4 years). There was a strong association between presence of stoma and (1) worse physical function (standardized MD = 0.7; 95% CI 0.21–1.19; I 2 = 95) and (2) worse quality of life (standardized MD = 1.61; 95% CI 0.5–2.72, I 2 = 98). The same effect was seen in fecal ostomy and urinary diversion. Few studies measured stoma independence and only one examined factors affecting this. No studies examined length of stay. Conclusions: Stoma have a negative association with the physical function and quality of life of older people. Future studies should focus on identifying modifiable factors that may affect physical function, quality of life, and stoma independence.